UPAYA GURU AGAMA DALAM MENANGGULANGI KENAKALAN REMAJA/SISWA DI SMP WACHID HASYIM PAMEKASAN - Muhammad Kholil (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
Teenagers are the people to come. Can be predicted that the picture of adolescents now is a reflection of society to come, both the bad shape and composition of society, moral and intellectual structure, in the appreciation of religious knowledge, national awareness, and the degree of advancement in behavior and personality among future communities depends on adolescents now, and the hope for the future lies with his sons and daughters, so that almost everyone wishes that their sons and daughters will become useful people.